Drought Resilience Debt Drives NPP Decline in the Amazon Forest - Machado‐Silva, Fausto; Peres, Leonardo F.; Gouveia, Celia M.; Enrich‐Prast, Alex; Peixoto, Roberta B.; Pereira, José M. C.; Marotta, Humberto; Fernandes, Pedro J. F.; Libonati, Renata (Global biogeochemical cycles, 2021)
Climate change has substantially increased the frequency of extreme droughts in the Amazon basin, generating concern about impacts on the world's largest tropical forest, which contributes about one‐seventh of the global vegetation carbon sink. Most research to understand drought impacts has focused on the immediate influences of such events, neglecting post‐drought effects on ecosystems recovery. Since ecological processes are influenced by antecedent conditions, we analyzed whether extreme droughts affect vegetation growth (i.e., net primary productivity, NPP) recovery. Here, we evaluated the NPP in the Amazon basin from 2003 to 2020, a period in which drought frequency was almost double the decadal incidence of the last century. We show that NPP does respond to the coupled impacts of individual droughts and the post‐drought impacts during ecosystem recovery. In particular, our results reveal that the ecosystems undergoing recovery show NPP about 13% lower than reference values based on the pre‐drought state or in areas undisturbed by drought. NPP deficits have consistently increased with the extreme droughts of 2005, 2010, and 2015 due to the combined effects of disturbances magnitude and the length of recovery. If the expected increase in drought frequency and intensity does occur, reduced recovery may lead the Amazon Forest to an alternative ecosystem state with lower carbon uptake, contributing to a warming global climate. Plain Language Summary Extreme droughts cause significant impacts on forest systems. Although drought disturbances are widely quantified, few studies address the impacts of post‐drought effects during the recovery period. In this work, we show that forests undergoing post‐drought recovery show lower levels of productivity than undisturbed systems. Recovery debts vary with drought intensity and the recovery time after each event. Global warming is projected to increase drought intensity and frequency worldwide and recovery debts may promote a decrease in forests carbon uptake. Key Points Forests undergoing post‐drought recovery show lower levels of productivity than undisturbed systems Recovery debts vary not only with the degree of intensity of the drought but also with the recovery time after each event